2018
DOI: 10.5603/kp.a2017.0187
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in antineutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis

Abstract: She is a member of the Polish Internal Medicine Society and a board member of the Polish Family Medicine Society. She is also a member of the College of Family Physicians in Poland and of the Association of Medical Education in Europe. Her main research areas are systemic vasculitis and nephrology. She has been published in leading international medical journals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(55 reference statements)
1
0
0
Order By: Relevance
“…Several studies have previously shown that traditional cardiovascular risk factors, including dyslipidemia, hypertension, and metabolic syndrome, are more common in AAV patients. [ 19 , 20 ] In our patient cohort, the prevalence of hypertension was more common, as expected. There was no significant difference in LDL-C and HDL-C levels between the patient and control groups; however, triglyceride levels were higher in the patient group.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have previously shown that traditional cardiovascular risk factors, including dyslipidemia, hypertension, and metabolic syndrome, are more common in AAV patients. [ 19 , 20 ] In our patient cohort, the prevalence of hypertension was more common, as expected. There was no significant difference in LDL-C and HDL-C levels between the patient and control groups; however, triglyceride levels were higher in the patient group.…”
Section: Discussionsupporting
confidence: 85%